Thermodynamic properties and intermolecular interaction of binary liquid mixtures of isopropanol with diethylenetriamine - Zhang, Jingxiao; Wang, Ye; Xie, Lin; Wang, Yiting; Zhong, Qiang; Zhang, Lilei (Thermochimica acta, 2025)
•Non-ideal IPA-DETA behavior driven by H-bonding and H-transfer interactions.•The excess properties of IPA-DETA reveal intermolecular interactions.•MD/quantum calculations confirm IPA hydroxyl‑DETA amino H-bond networks.•Low-energy H-transfer between IPA and DETA validated via IR/¹H NMR spectroscopy. This study investigates the thermophysical properties and molecular interactions in the binary system of isopropanol (IPA) and diethylenetriamine (DETA) over a range of temperatures and compositions. Experimental measurements of density, viscosity, speed of sound, and their derived properties revealed significant non-ideal behavior attributed to intermolecular interactions, particularly hydrogen bonding. Theoretical calculations, including molecular dynamics simulations and quantum chemical analyses, identified the phenomenon of hydrogen transfer between the hydroxyl group of IPA and the amino groups of DETA, with low activation energies facilitating this process. Characterization by 1H NMR and IR spectroscopy further confirmed these interactions, highlighting the role of hydrogen bonding and its impact on the system's macroscopic properties. These findings provide new insights into the interplay of molecular interactions in alcohol-amine binary mixtures and their role in governing CO₂ absorption performance. [Display omitted]